1965
DOI: 10.1039/jr9650003599
|View full text |Cite
|
Sign up to set email alerts
|

660. The chlorination of some n-alkanes and alkyl chlorides

Abstract: The liquid-phase chlorination of n-hexane, n-octane, 1-, 2-, and 3-chlorohexane, and l-chloro-octane, using elemental chlorine, has been studied a t 20". Product yields of the mono and higher chlorides, together with unreacted n-hexane, have been compared with a statistical rrAodel for the chlorination of alkanes. The overall reactivities of the individual reactants have been measured, relative to n-hexane, and are in the order: n-octane > n-hexane = l-chloro-octane > l-chlorohexane > 2-chlorohexane > 3-chloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Activated sludge from a sewage treatment plant, acclimated to n-hexadecane for 60 days, dechlorinated only 2% of a medium chain PCA (C 15.4 Cl 5.6 ). Fisk et al [36] found that four 14 C-labeled PCAs (two C 12 (56% and 69% Cl) and two C 16 (35% and 69% Cl) PCAs) were degraded at 12°C in aerobic sediments used for a study of bioavailability of PCAs in oligochaetes. Half lives of the C 12 -PCAs in sediment were 13 days and 30 days for the 56% and 69% Cl products, respectively, while for the C 16 -PCA, half lives of 12 days and 58 days for 35% and 69% Cl PCAs were observed.…”
Section: Microbial Biodegradationmentioning
confidence: 98%
See 2 more Smart Citations
“…Activated sludge from a sewage treatment plant, acclimated to n-hexadecane for 60 days, dechlorinated only 2% of a medium chain PCA (C 15.4 Cl 5.6 ). Fisk et al [36] found that four 14 C-labeled PCAs (two C 12 (56% and 69% Cl) and two C 16 (35% and 69% Cl) PCAs) were degraded at 12°C in aerobic sediments used for a study of bioavailability of PCAs in oligochaetes. Half lives of the C 12 -PCAs in sediment were 13 days and 30 days for the 56% and 69% Cl products, respectively, while for the C 16 -PCA, half lives of 12 days and 58 days for 35% and 69% Cl PCAs were observed.…”
Section: Microbial Biodegradationmentioning
confidence: 98%
“…However, in general, HLC values for PCAs do not show the large [22]. Reverse phase HPLC analysis of C 16 PCAs also yields log K OW values close to the range predicted by fragment constants [36]. Octanol-air partition coefficients of PCAs have not been measured directly but they can be estimated from the ratio of K OW /K AW (where K AW = unitless airwater partition coefficient).…”
Section: Water Solubility Vapor Pressures and Henry's Law Constantmentioning
confidence: 99%
See 1 more Smart Citation
“…The dispersed chlorination mode of alkanes decides that the dihedral angle (H-C-C-Cl) receives the preference over (Cl-C-C-Cl) in hexa-and heptachloro-decanes, the predominant isomers in commercial SCCPs [9,33]. Therefore, the potential energy profiles for intramolecular rotation of the dihedral angles (H-C-C-Cl) were calculated at the B3LYP/6-311++G(d,p) level to shed more light on the influence of different intramolecular NCIs on the conformations of the two molecules.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the dihedral angle (H-C-C-Cl) receives the preference over (Cl-C-C-Cl) in SCCPs due to its dispersed chlorination modes [9,33], the potential energy profiles for intramolecular rotation of the dihedral angles (H-C-C-Cl) for 5,5,6,6-tetrachlorodecane and 4,4,6,6-tetrachlorodecane have been calculated with (H-C-C-Cl) initially assigned the value 0°, respectively, to shed more light on the conformation preference of the two molecules ( Figure 1). The H-C-C-Cl dihedral angles are switched every 10° to obtain one starting geometry.…”
Section: The Potential Energy Profiles For Intramolecular Rotation Ofmentioning
confidence: 99%